IMPLEMENTATION OF THE RELOCATION POLICY FOR STREET VENDORS IN MALIOBORO, INDONESIA: THE ROLE AND CHALLENGES OF LOCAL GOVERNMENT IN IMPLEMENTATION - Cellinia Rani Astica; Tyas Nanda Prastina; Arzheti Rosinta Mayanti; Syavina Mayang Alifiani; Anggara Setya Saputra (DYNAMICS: Journal Of Public Administration, 2025)
The street vendor (PKL) relocation policy in Malioboro, Yogyakarta, addresses public space disorder, traffic congestion, and aesthetic disruptions in a key tourism area, where PKL play a crucial role in the informal economy yet pose urban challenges. This study aims to evaluate the role and challenges of the DIY Regional Government in its implementation using the Van Meter and Van Horn model, employing a qualitative literature review method from national scientific journals. Findings reveal partial success through enhanced pedestrian orderliness, adequate facilities like permanent stalls and security at Teras Malioboro 1-2, supported by regulations such as Governor's Circular No. 3/SE/2022, despite obstacles like post-pandemic income decline, initial resistance, and immature initial facilities. Compared to failures in Purbalingga, Surabaya, and Sidoarjo, Malioboro excels due to intensive socialization and inter-agency coordination. The conclusion recommends participatory approaches, business-suited facilities, and ongoing monitoring for sustainable PKL economics and inclusive urban ordering.